Problematika Historiografi Nasional Indonesia - Rofiq, Achmad Choirul (Qurthuba: The Journal of History and Islamic Civilization, 2017)
The significance of history for human life is shown by the use of history as a teacher of life in the future. Because of that historical significance, many communities and nations intensified the writing of history to show their identity and build character of their people. Indonesia also has national history writing, although there are historical problems caused by the political interests of the ruling government. Academic anxiety then appeared among historians that promote objectivity. After the collapse of the New Order regime, a strong desire raised to publish the latest national history (Indonesia dalam Arus Sejarah) in order to fill the shortage of Sejarah Nasional Indonesia. Nevertheless, a reading of Indonesia dalam Arus Sejarah shows that this book has not answered yet all of those historical problems, such as the role of Pattimura and Si Singamangaraja XII in the fight against colonialism, the role of Budi Utomo in the national revival, the role Sjafruddin Prawiranegara and Assaat in the struggle for Indonesian independence, as well as the Movement of 30 September 1965 (G-30-S / PKI). Therefore, Indonesian historians have a moral obligation to make recommendations to the government to review the policy of the government that has very weak historical bases to give historical enlightenment to Indonesian people. In spite of it, the writing of Indonesia dalam Arus Sejarah should be appreciated because the writers have included many themes that were previously not found in Sejarah Nasional Indonesia.